Effect of supplementation on nutrient digestibility and performance of lactating calves fed with Brachiaria brizantha pastures - DOI: 10.4025/actascianimsci.v32i1.4849 - Sampaio, Alexandre Amstalden Moraes (2009)
This study evaluated the effect of supplementation and the type of supplement on nutrient digestibility and performance of lactating calves fed with Brachiara brizantha cv. Marandu pasture from February to May. The treatments were: supplementation in creep-feeding with protein concentrate, with energy concentrate, with energy-protein concentrate and without concentrate. In a Latin square design, four Canchim calves were kept in individual pens, receiving marandu hay and controlled suckling twice a day. The performance was evaluated in a completely randomized design, with 23 calves kept with the cows. Higher intake and nutrients digestibility (65% of dry mater digestibility) and calf performance (live weight gain of 0.98 kg day-1) were obtained with energy-protein concentrate, and the cows kept weight and body reserves during the experiment. The protein concentrate did not show good results, and was lower than the performance of calves without supplementation – 0.56 and 0.77 kg day-1, respectively. The performance of calves without supplementation was similar to calves receiving energy concentrate, but the cows lost more body weight and energy reserves. The supplementation with energy-protein concentrate for lactating calves fed with Brachiara brizantha cv. Marandu during the beginning of the dry season was benefifical for the performance of calves and cows